2006
DOI: 10.1007/s10067-006-0439-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and quality of life in arthritis: a population-based study

Abstract: Previous studies using clinic or convenience samples have indicated that not only patients with arthritis are at increased risk of depression, but there may also be a link between depression and disability in people with arthritis. We examined the prevalence of psychological distress in a population sample with and without arthritis and the association with health-related quality of life. The WANTS Health and Well-being Survey was a population household telephone interview survey of adults (age > or =18 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
4
35
0
1
Order By: Relevance
“…For some patients, RA also negatively influenced partnerships in no longer being able to enjoy cuddling and sex, or in losing a companionship that was previously based on conducting recreational activities together. Negative emotions in relation to RA have been previously described [16,17,30,31,37]. Hill et al [31] found that one-third of RA patients experienced adversely affected relationships.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For some patients, RA also negatively influenced partnerships in no longer being able to enjoy cuddling and sex, or in losing a companionship that was previously based on conducting recreational activities together. Negative emotions in relation to RA have been previously described [16,17,30,31,37]. Hill et al [31] found that one-third of RA patients experienced adversely affected relationships.…”
Section: Discussionmentioning
confidence: 94%
“…Negative emotions in relation to RA have been previously described [16,17,30,31,37]. Hill et al [31] found that one-third of RA patients experienced adversely affected relationships. In a recent focus group study on fatigue in RA patients, participants expressed that they had become hard live with due to their experienced negative emotions: sense of hopelessness, shame, anger and irritability, and fear [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the interim, given that anxiety is commonly associated with chronic physical conditions such as osteoarthritis (Scott et al, 2007;Wu et al, 2002), and that anxiety may contribute to pain, pain-related fears and negative functional outcomes (Heuts et al, 2004), as well as indirectly to some forms of osteoarthritis as a result of injury (Lavallee & Flint, 1996), there is clearly a strong to prevent anxiety where this can be predicted, as well as a strong imperative to identify anxiety where it exists, and as to clearly characterize its specific nature, and better understand its etiology and temporal dimensions, in order to intervene effectively in the context of this disease. To this end Hill et al (2007) emphasized that physicians need to recognize as well as address the significant additional negative impact anxiety can render on the patients' physical well being. In addition, Dorr and Chao (2007), who found that the pre-surgical emotional state of the patient undergoing joint replacement surgery affected their feelings of satisfaction after surgery, advocated for appropriate preoperative education to allay any unwarranted negative impact.…”
mentioning
confidence: 99%
“…However, cost savings and vastly improved health outcomes including physical health, social functioning, and increased health-related quality of life are predicted in the long term (Katon et al, 2007). Indeed, as outlined by Hill et al (2007) and Perrucio et al (2011), because optimal mental well-being is critical for maximizing conservative as well as replacement surgery outcomes for patients with osteoarthritis, an exclusive focus on physical health that leads to missed opportunities for recognizing and successfully enhancing opportunities to improve the patient's overall health status, will not only increase economic costs, but the immense social costs of the disease, as well.…”
mentioning
confidence: 99%